Continuous model applied to multi-disk and multi-bearing rotors. (27th October 2022) - Mereles, Arthur; Alves, Diogo Stuani; Cavalca, Katia Lucchesi
Abstract: This work aims at presenting a modeling approach to solve problems in rotordynamics. The method, named Continuous Segment Method (CSM), is valid for systems with several stepped sections and multiple disks and bearings. The shaft is modeled using 1D beam theory, and takes into account gyroscopic effect, rotary inertia and shear deformation. The disks are modeled as concentrated masses with rotary inertia and the bearings can be anisotropic with either long or short characteristics. Long bearings are modeled as elastic foundations whereas short bearings as point-wise spring–damper systems. The basis of the method consist in solving the eigenvalue problem of the system and use the eigenfunctions and eigenvalues to apply modal analysis to discretize the equations of motions. The eigenvalue problem is solved by, firstly, dividing the domain and obtaining local problems. The solution of these, and the use of continuity conditions, allows the obtention of global eigenfunctions and eigenvalues. The evaluation of the CSM is done by comparing its results with the Finite Element Method (FEM) for three applications that are common in rotordynamics: obtention of natural frequencies and mode shapes, response to unbalance and to nonlinear forces. The comparison with the FEM shows that the CSM can be seen as a promising alternative to model complex rotor systems. Highlights: This paper presents a method to model rotors with multiple disks and bearings. The shaft is modeled as a beam with rotary inertia and shear deformation. The bearings can be anisotropic with either short or long characteristics. The method presents an approach to discretize the continuous system. Evaluation of the method is done by comparing with the finite element method.